Current Treatment Strategies in Cutaneous Malignant Melanoma of the Head and Neck - ÖZGÜR, Erdoğan; KARAKULLUKÇU, Barış; ESKİİZMİR, Görkem (ENT Updates, 2019)
Cutaneous malignant melanoma is potentially an important health problem for white people. The incidence of melanoma is rising faster than other solid cancers. Despite the new melanoma drugs surgery for localised melanoma and regional metastasis is still the standard of care. However management of cutaneous melanoma differs from other cancers at some points such as biopsy technique, surgical margine, incorporation ofsentinel lymph node biopsy for staging etc. In this review we focused on the role of the head and neck surgeon in management of cutaneous melanoma of head and neck region according to current knowledge.